PENGARUH SELF EFFICACY, PERFORMANCE EXPECTANCY, EFFORT EXPECTANCY, DAN SOCIAL INFLUENCE TERHADAP NIAT PENGGUNAAN E-WALLET PADA UMKM KECAMATAN GEMOLONG - Muhammad Celebastian Sugiarto; Imronudin (JURNAL LENTERA BISNIS, 2024)
The purpose of this study is to analyze self-efficacy, performance expectancy, effort expectancy and social influence on the behavioural intention of MSME players in Gemolong Subdistrict to adopt e-wallet. This study uses quantitative research methods, more than 200 questionnaires were distributed to MSME players in Gemolong Subdistrict and 170 were responded obtained to assess the reliability and validity of the instrument. This study uses Partial Least Square Technique using SMARTPLS app. This study found that self-efficacy has a significant influence into e-wallet behaviour intention, the performance expectancy variable found has a significant influence into behaviour intention of e-wallet, the effort expectancy variable wasn’t have significant influence into behavioural intention of e-wallet, and social influence variable found that have a significant influence on behavioural intention of e-wallet.